2018
DOI: 10.1186/s13046-018-0941-x
|View full text |Cite
|
Sign up to set email alerts
|

Over-expressed lncRNA HOTAIRM1 promotes tumor growth and invasion through up-regulating HOXA1 and sequestering G9a/EZH2/Dnmts away from the HOXA1 gene in glioblastoma multiforme

Abstract: BackgroundGlioblastoma multiforme (GBM) is the common primary brain tumor classified the most malignant glioma. Long non-coding RNAs (LncRNAs) are important epigenetic regulators with critical roles in cancer initiation and progression. LncRNA HOTAIRM1 transcribes from the antisense strand of HOXA gene cluster which locus in chromosome 7p15.2. Recent studies have shown that HOTAIRM1 is involved in acute myeloid leukemia and colorectal cancer. Here we sought to investigate the role of HOTAIRM1 in GBM and explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
115
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 41 publications
9
115
1
Order By: Relevance
“…HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) is a lncRNA with a length of 1052 bp. It was recently found to participate in various cancers, such as gastrointestinal malignancies [13][14][15][16] , breast cancer 17 , lung cancer 18 , glioblastoma multiforme 19 , and acute myeloid leukemia 20,21 . Of note, HOTAIRM1 is under-expressed in colorectal cancer 13 and gastric cancer 14 .…”
Section: Introductionmentioning
confidence: 99%
“…HOX antisense intergenic RNA myeloid 1 (HOTAIRM1) is a lncRNA with a length of 1052 bp. It was recently found to participate in various cancers, such as gastrointestinal malignancies [13][14][15][16] , breast cancer 17 , lung cancer 18 , glioblastoma multiforme 19 , and acute myeloid leukemia 20,21 . Of note, HOTAIRM1 is under-expressed in colorectal cancer 13 and gastric cancer 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lncRNAs have been commonly acknowledged to affect a variety of biological processes, such as regulating proliferation and apoptosis and reprogramming the pluripotency of stem cells. As recently reported, lncRNA can act as a tumour facilitator or suppressor in cancers 10,11. These results revealed that lncRNAs exhibited pivotal functions in regulating genome.…”
Section: Introductionsupporting
confidence: 76%
“…For example, knockdown of the lncRNA HMMR‐AS1 inhibits the proliferation of GBM and increases its sensitivity to chemotherap 4 . High expression of the oncogene HOTAIRM1 can promote the proliferation and migration of GBM cells, which can be achieved through the regulation of HOXA1 5 . MNX1‐AS1 antagonizes miR‐4443 through competitive inhibition and thereby increases GBM proliferation and migration 6 .…”
Section: Introductionmentioning
confidence: 99%